Treat and Extend – an Effective Strategy for Treatment of Exudative Age-related Macular Degeneration - Dolar-Szczasny, Joanna; Święch, Anna (Klinika Oczna / Acta Ophthalmologica Polonica, 2019)
This paper discusses the validity of different dosing regimens with anti-vascular endothelial growth factor iniections for neovascular age-related macular degeneration. After the initial trials of anti- vascular endothelial growth factor therapy, the variable dosing regimens such as continuous fixed dosing and pro re nata were implemented. Treat-and-Extend, a recently introduced regimen, aimed to optimize the anti-vascular endothelial growth factor treatment strategy for neovascular age-related macular degeneration. The Treat-and-Extend scheme uses an extending interval approach and has become widely approved for the minimized number of control visits required and its effectiveness. Studies investigating the Treat-and-Extend strategy also showed that this could allow for reduction of clinical burden and good outcomes, thus meeting the real-life requirements. This progressive development of variable dosing regimens is a response to the real-life circumstances of limited human, technical, and financial resources. This includes optimization of the number of iniections, a minimal number of monitoring visits, and ease of planning ahead. The Treat-and-Extend regimen achieves this goal with good functional results.